The Understanding of Intentions, Desires and Beliefs in Young Children with Autism Spectrum Disorder - Broekhof, Evelien (J Autism Dev Disord, 2015)
This study provides a comprehensive picture of three core elements (Intentions, Desires, Beliefs) of Theory of Mind (ToM) in young children with autism spectrum disorder (ASD, n = 63, Mage = 55 months) and typically developing children (TD, n = 69, Mage = 54 months). Outcomes showed that ASD and TD children understood intentional actions equally well. Yet, children with ASD lacked the social interest to share intentions. Additionally, children with ASD had more difficulties in understanding others’ desires and beliefs compared to their TD peers. It is discussed whether the ToM delay seen in children with ASD is a motivational or a conceptual problem.